1991
DOI: 10.1017/s0950268800048500
|View full text |Cite
|
Sign up to set email alerts
|

Chronic atrophic oral candidiasis among patients with diabetes mellitus – role of secretor status

Abstract: SUMMARYNon-diabetic individuals who are non-secretors of blood group antigens are prone to superficial infections by Candida albicans. In this study, 216 patients with diabetes mellitus who were denture wearers were examined for the presence or absence of denture stomatitis. There was an overall trend for non-secretors to be prone to denture stomatitis compared with secretors. Stepwise linear discriminant analysis was used to dissect the contribution of secretor status and other variables to the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
2

Year Published

1992
1992
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 12 publications
3
15
2
Order By: Relevance
“…These results are similar to studies which found 60 % of isolates from diabetics to be C. albicans [3,16]. This emphasizes the need for accurate identification as patients with diabetes are more likely to carry and to have disease due to species other than C. albicans [18] which might not be sensitive to routinely prescribed oral antifungal agents [19]. The third objective was to assess the association between secretor status and carriage of yeasts among individuals with IDDM separately from those with NIDDM.…”
Section: Discussionsupporting
confidence: 78%
“…These results are similar to studies which found 60 % of isolates from diabetics to be C. albicans [3,16]. This emphasizes the need for accurate identification as patients with diabetes are more likely to carry and to have disease due to species other than C. albicans [18] which might not be sensitive to routinely prescribed oral antifungal agents [19]. The third objective was to assess the association between secretor status and carriage of yeasts among individuals with IDDM separately from those with NIDDM.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, C. glabrata and C. tropicalis were isolated mainly from diabetic patients carriers of dentures. 1,7 In our study, we found in mouthwash from DM, GDM, CON, both higher prevalence of C. albicans (77.3%, 79.3%, 70.0%, respectively) and C. glabrata (13.6%, 6.9%, 10.9%, respectively). These data are supported by another Polish study where in oral cavity of non-diabetics C. glabrata was found in 20 -66%.…”
Section: Discussionsupporting
confidence: 47%
“…Accurate identification of strains isolated from diabetic patients is especially important because they are more likely to carry species other than C. albicans which might not be sensitive to certain antifungal agents. 1,7 Recently, Goswami et al reported that C. glabrata (39%) was a predominant species isolated from vagina of diabetic Indian women and C. albicans was detected only in 26%. Surprisingly, in healthy women C. glabrata was as frequent as C. albicans (30%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations